Electrical resistivity of Ti₄₁.₅Zr₄₁.₅Ni₁₇ quasicrystals in the temperature region 0.3–300 K - Azhazha, V.M.; Khadzhay, G.Ya.; Malikhin, S.V.; Merisov, B.A.; Ott, H.R.; Pugachov, A.T.; Sologubenko, A.V. (Физика низких температур, 2005)
The electrical resistivity of icosahedral quasicrystals Ti₄₁.₅Zr₄₁.₅Ni₁₇ was investigated in the temperature region between 0.3 and 300 K on samples of different quality. In the temperature region between 0.3 and 2 K, the influence of external magnetic fields up to 16 kOe on the superconducting transition of these materials was investigated. The temperature dependence of the resistivity in the region of the superconducting transition varies in a step-like manner. The data of the x-ray analysis imply the presence of several different quasicrystalline phases. Above the superconducting transition, a resistivity minimum is observed.